Modeling and simulation of a nonliner active suspension system using a controller - Ramli, Nurulhani (2011)
This proposal presents a mathematical model and control law of a nonlinear active suspension system. The goal of active suspension system is to control the vehicle's body even though with the occulrence of driver's and road perturbation. The perturbation tends to degrade the performance of active suspension systems which introduce harshness to the ride quality and reducing off-road mobility. Since the characteristics of spring, damping force and the road model are mostly nonlinear, the suspension system is thorny to control. The objective of designing the active suspension system's controller is to control the suspension forces to suit the road and driving conditions. The controller will improve the performance of the nonlinear active suspension system.